1967
DOI: 10.1038/icb.1967.67
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Heterogeneity of Macrophages at the Single Cell Level

Abstract: Summary A study has been made of the ability of mouse peritoneal macrophages to phagocytose and kill Salmonella typhimurium and Listeria monocytogenes. This study, carried out at a single cell level, indicates that the competence of the population of macrophages may be altered by various treatments but the expression of this competence is dependent on the presence of specific antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Microscopy and FACS revealed diverse phenotypes, including uninfected cells and cells infected with single or multiple, live (yellow) or dead (red) bacteria, as has been previously described (McIntrye et al, 1967) ( Figures 1B, 1C ). This variability is neither simply a transient phenomenon nor a mere outcome of the specific MOI chosen, since it is sustained throughout the 24 hour time course ( Figure S1B ) and with increasing MOI ( Figure S1C ).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Microscopy and FACS revealed diverse phenotypes, including uninfected cells and cells infected with single or multiple, live (yellow) or dead (red) bacteria, as has been previously described (McIntrye et al, 1967) ( Figures 1B, 1C ). This variability is neither simply a transient phenomenon nor a mere outcome of the specific MOI chosen, since it is sustained throughout the 24 hour time course ( Figure S1B ) and with increasing MOI ( Figure S1C ).…”
Section: Resultssupporting
confidence: 72%
“…Indeed, infection of macrophages with Salmonella generates well-documented diverse outcomes: some macrophages engulf the bacteria, while others remain uninfected (McIntrye et al, 1967); some macrophages lyse the ingested bacteria, while others are permissive to intracellular bacterial survival (McIntrye et al, 1967); some macrophages will undergo cell death with bacterial release (Monack et al, 1996), while others survive and allow bacteria to multiply or persist intracellularly (Helaine et al, 2010). Despite longstanding observations of these diverse outcomes however, we currently lack an understanding of the underlying molecular mechanisms in either the host or pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…For technical reasons the anti-microbial potential of activated macrophages in vitro has been less extensively studied. McZntyre et al [85] found a wide variation in the bactericidal capacity of individual macrophages. In limited studies we have found that smaller macrophages, separated by sedimentation velocity, are somewhat more potent than larger cells in killing Salmonella enteritidis in vitro [54].…”
Section: Activationmentioning
confidence: 99%
“…McIntyre et al [85] found a wide variation in the bactericidal capacity of individual macro phages. In limited studies we have found that smaller macrophages, separated by sed imentation velocity, are somewhat more po tent than larger cells in killing Salmonella enteritidis in vitro [54].…”
Section: Activationmentioning
confidence: 99%